Comparative Perspectives on Non-Conviction Based Asset Forfeiture: Legal Frameworks and Practices in Indonesia, United States, and United Kingdom - Hanifah Azizah; Topo Santoso; Yunus Husein; Mahmud Mulyadi (Proceedings Series on Social Sciences & Humanities, 2023)
One of the most crucial instruments in fighting against corruption, money laundering, and transnational organized crime is non-conviction-based asset forfeiture, or NCB-AF. The seizure of assets linked to illegal activity is permitted under this mechanism without a prior criminal conviction, on the condition that robust due process protections are maintained. Using international standards such as the UN Convention Against Corruption (UNCAC), the United Nations Convention Against Transnational Organized Crime (UN-CATOC), and the Financial Action Task Force's ( FATF) recommendations, this research aims to analyze the NCB-AF laws and regulations in the following selected nations: the United States and the United Kingdom. The main research question is twofold: first, to examine the practical application and effectiveness of NCB-AF mechanisms in selected jurisdictions; and second, to synthesize key insights from these comparative models to inform the development of a robust NCB-AF framework in Indonesia. This research applies normative legal analysis through a comparative legal framework. The results show that there are many different types of models, such as civil in rem proceedings, unexplained wealth regimes, and reverse onus provisions. While NCB-AF has proven effective in asset recovery and disrupting criminal enterprises, it raises concerns regarding human rights safeguards and international cooperation. The study suggests that Indonesia should design a balanced NCB-AF framework that harmonizes international standards with constitutional protections.